TMS-induced neural noise in sensory cortex interferes with short-term memory storage in prefrontal cortex - Bancroft, Tyler D.; Hogeveen, Jeremy; Hockley, William E.; Servos, Philip (Frontiers in Computational Neuroscience, 2014)
In a previous study, Harris et al. (2002) found disruption of vibrotactile short-term memory after applying single-pulse transcranial magnetic stimulation to primary somatosensory cortex (SI) early in the maintenance period, and suggested that this demonstrated a role for SI in vibrotactile memory storage. While such a role is compatible with recent suggestions that sensory cortex is the storage substrate for working memory, it stands in contrast to a relatively large body of evidence from human EEG and single-cell recording in primates that instead points to prefrontal cortex as the storage substrate for vibrotactile memory. In the present study, we use computational methods to demonstrate how Harris et al.’s results can be reproduced by TMS-induced activity in sensory cortex and subsequent feedforward interference with memory traces stored in prefrontal cortex, thereby reconciling discordant findings in the tactile memory literature.